2017
DOI: 10.1111/oik.04714
|View full text |Cite
|
Sign up to set email alerts
|

Facultative paedomorphosis as a mechanism promoting intraspecific niche differentiation

Abstract: Organisms with complex life cycles are characterized by a metamorphosis that allows for a major habitat shift and the exploitation of alternative resources. However, metamorphosis can be bypassed in some species through a process called paedomorphosis, resulting in the retention of larval traits at the adult stage and is considered important at both micro‐ and macroevolutionary scales. In facultatively paedomorphic populations of newts, some individuals retain gills and a fully aquatic life at the adult stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 81 publications
(109 reference statements)
0
23
0
Order By: Relevance
“…, Lejeune et al. ). Unfortunately, the longer persistence of metamorphs proved to be, in most cases, only a transient state, given that in the last years they showed a pattern of decline comparable to the one of paedomorphs in the 2000s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Lejeune et al. ). Unfortunately, the longer persistence of metamorphs proved to be, in most cases, only a transient state, given that in the last years they showed a pattern of decline comparable to the one of paedomorphs in the 2000s.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been suggested that metamorphs in water bodies with fish could come from nearby fishless ones, i.e., through a source-sink dynamic process (Breuil 1985). Third, paedomorphic newts are more pelagic than metamorphs and, therefore, are more easily preyed upon by large predators such as salmonids (Deno€ el et al 2005b, Lejeune et al 2018. Unfortunately, the longer persistence of metamorphs proved to be, in most cases, only a transient state, given that in the last years they showed a pattern of decline comparable to the one of paedomorphs in the 2000s.…”
Section: Anthropogenic Pressures On Freshwater Habitats and Amphibiansmentioning
confidence: 99%
“…Next to different capabilities for capturing elusive prey, also different prey preferences were found between morphs [11, 15]. Furthermore, it has been shown that paedomorphic and metamorphic Alpine newts from the same population partition their trophic habitats [14, 45]. Depending on size and heterogeneity of habitats, paedomorphs tend to live in the entire water column and deep benthic areas where they mainly capture small elusive prey, such as Daphnia and other small pelagic invertebrates while metamorphs live close to the shoreline and mainly rely on terrestrial arthropods that fell into the water [14].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably partly because non-lethal sampling methods are rarely used (but see e.g. Sepulveda et al, 2012;Gillespie, 2013;Remon et al, 2016, Lejeune et al, 2018. Only one study thoroughly explored the relevance of tail clips (i.e.…”
Section: Introductionmentioning
confidence: 99%